2018
DOI: 10.17576/jsm-2018-4711-16
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Palm Tocotrienol on Surface Osteoblast and Osteoclast in Excess Glucocorticoid Osteoporotic Rat Model

Abstract: A balanced interaction between osteoblast and osteoclast plays a major role in maintaining bone strength and structural integrity. Tocotrienol, a palm derivative with potent antioxidant properties showed an anti-osteoporotic effect but little is known about its mechanism of action. Hence, this research was conducted to determine the effects of palm tocotrienol on the surface osteoblast and osteoclast of the the glucocorticoid-induced osteoporotic bones. The study involved 40 male Sprague-Dawley rats weighing 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These results suggest that ATT and PTT could suppress the high bone remodelling phenotype commonly observed with osteoporosis. ATT also increased the osterix expression in the femur in GC-induced osteoporotic rats [58], suggesting that ATT might improve osteoblast differentiation and maturation [78].…”
Section: Tocotrienol and Bonementioning
confidence: 89%
“…These results suggest that ATT and PTT could suppress the high bone remodelling phenotype commonly observed with osteoporosis. ATT also increased the osterix expression in the femur in GC-induced osteoporotic rats [58], suggesting that ATT might improve osteoblast differentiation and maturation [78].…”
Section: Tocotrienol and Bonementioning
confidence: 89%
“…Our study demonstrated that both vitamin E-supplemented groups showed an upregulation of both M-CFS and RANKL, but both supplemented groups showed a notable decrease in expression when compared with NC group demonstrating the potential of tocotrienol and tocopherol in regulating osteoclastogenesis. The role of vitamin E in bone-related diseases such as the action of osteoclast inhibition and bone resorption reduction activity has been widely published in previous studies (69,70). However, the relationship between bone and cancer remains undefined in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Tocotrienols have been widely studied for their antioxidant properties in bone and in other diseases [ 43 , 44 , 45 , 46 ]. Our previous work has shown that tocotrienols are beneficial for bone health because they can promote bone regeneration both in vitro [ 47 , 48 ] and in vivo [ 49 , 50 , 51 ]. In a systematic review by Radzi et al (2018), it was concluded that TRF is able to decrease resorption activity, but not osteoclastogenesis [ 52 ].…”
Section: Introductionmentioning
confidence: 99%